Characteristics of Complaints of Workers in Noise Professions with Auditory Impairments - Nasretdinova M.T; Raupova K.M; Bekmuradov M.A; Davronov U.F (Genius Journals, 2024)
The authors performed the examination of 230 workers whose exposure to noisy working environment ranged from 1 to 30 years and of 30 normal-hearing persons who were not exposed to noise. Tonal threshold, suprathreshold and speech audiometry were made using the audiometer MA-31 (GDR). Rheoencephalographic and thermographic studies were also performed. The examined persons were divided into 6 groups according to the hearing function state. Decreased hearing level and tinnitus were marked in all the persons with disturbed hearing function irrespectively of the duration of service in the noisy environment. Analysis of complaints of “noisy” workers suggested that there is a relationship of these complaints to the state of the cerebral circulation and hearing function.
Keywords: nervous system; tinnitus; dizziness; headache